2012
DOI: 10.1248/bpb.35.289
|View full text |Cite
|
Sign up to set email alerts
|

Kalopanaxsaponin A Inhibits the Invasion of Human Oral Squamous Cell Carcinoma by Reducing Metalloproteinase-9 mRNA Stability and Protein Trafficking

Abstract: Key words Kalopanaxsaponin-A; oral cancer; anti-invasive effect; metalloproteinase-9; HuR; Ras-associated binding 1AOral squamous cell carcinoma (OSCC) is a common malignant tumor in the oral and maxillofacial region, and it is the sixth most common cancer worldwide. In high-risk countries such as Sri Lanka, India, Pakistan, and Bangladesh, oral cancer may contribute up to 25% of all new cases of cancer, and in most countries, the five-year survival rates for cancers of the tongue, oral cavity and oropharynx a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 45 publications
0
30
0
1
Order By: Relevance
“…In CRC, previous studies indicate that the expression of MMP9 is associated with metastasis [18-20] and poor prognosis [21-23]. Interestingly, a recent study showed that Rab1A knockdown decreases MMP9 expression and inhibites MMP9-mediated invasiveness of human oral squamous cell cancer cells, suggesting that Rab1A regulates MMP9-mediated invasiveness [24]. Given the high homology between Rab1A and Rab1B, it would be interesting to determine whether Rab1B protein promotes invasiveness and metastasis by upregulating the expression of MMP9 in CRC.…”
Section: Introductionmentioning
confidence: 99%
“…In CRC, previous studies indicate that the expression of MMP9 is associated with metastasis [18-20] and poor prognosis [21-23]. Interestingly, a recent study showed that Rab1A knockdown decreases MMP9 expression and inhibites MMP9-mediated invasiveness of human oral squamous cell cancer cells, suggesting that Rab1A regulates MMP9-mediated invasiveness [24]. Given the high homology between Rab1A and Rab1B, it would be interesting to determine whether Rab1B protein promotes invasiveness and metastasis by upregulating the expression of MMP9 in CRC.…”
Section: Introductionmentioning
confidence: 99%
“…PMA is widely used as a tumor promoter for the stimulation of cell invasion in various types of cancer cells [36][37][38]. In PMA-treated YD-10B cells, mRNA expression and protein activation of MMP-2/-9 were highly inhibited in the hexane and chloroform fractions (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Besides the transcriptional regulation, mRNA stability also regulated the protein expressions of VEGF‐A and MMP‐9 42, 43, 44, 45. Carraway KR et al.…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated that CIL‐102 reduced MMP‐9 expression and invasion and migration of K562 cells through simultaneous suppression of MMP‐9 genetic transcription and mRNA stability 44. Hwang et al45 proved that Kalopanaxsaponin A inhibited the invasiveness of oral cancer by reducing MMP‐9 mRNA stability and expression. The present study demonstrated that overexpression of nucleolin enhanced that stability of VEGF‐A and MMP‐9 mRNA, vice versa.…”
Section: Discussionmentioning
confidence: 99%